Pengaruh Pemberian Buah Kurma terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri di MTs Negeri 5 Sragen - Jannur Annafi Rahayu; Siska Ningtyas Prabasari (Pusat Riset dan Inovasi Nasional, 2024)
Anemia is a condition in which there is a decrease in the number of erythrocytes in the blood indicated by a decrease in hemoglobin levels. In 2018 there was an increase of 13.6% from 2017. Which means that 3-4 out of 10 adolescents who experience anemia in adolescent girls, anemia can cause short-term effects such as decreased immunity, impaired concentration, decreased school performance, and menstrual problems. Dates can help prevent anemia because they are rich in iron and calcium, which are important for the formation of red blood cells and bone marrow. This type of research using Pre-experimental design with one group Pretest-Posttest. The population and sample in this study were adolescents with moderate anemia as many as 20 respondents. Sampling technique is Accidental Sampling and data collection is done by observation. Data analysis was performed using the Wilcoxon Test. Before given the dates of the lowest hemoglobin levels 8 gr/dl and the highest 10.9 gr/dl, after given the dates of the lowest hemoglobin levels 11 gr/dl and the highest 13.7 gr / dl. Wilcoxon test showed a P-Value of 0.000 that giving dates had a significant effect on increasing hemoglobin levels in adolescent girls in MTs Negeri 5 Sragen in 2024. There Is The Effect Of Giving Dates To Increase Hemoglobin Levels In Adolescent Girls In Mts Negeri 5 Sragen. Giving dates can be used as an additional alternative to iron to prevent anemia in adolescent girls in MTs Negeri 5 Sragen.